A systematic review of the clinicopathological characteristics of oral leiomyomatous hamartoma - Alarcón-Sánchez, Mario Alberto; Nava-Villalba, Mario; Escoto-Vasquez, Lilibeth-Stephania; Heboyan, Artak (World journal of surgical oncology, 2024)
Oral leiomyomatous hamartoma (OLH) corresponds to an abnormal, benign and disorganized overgrowth of mature smooth muscle tissue, which can develop in any site where this tissue is found in healthy conditions. The present systematic review aimed to analyze the clinicopathological characteristics of OLH. The protocol of this study was constructed following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) and was registered in the Open Science Framework (OSF): OSF.IO/BMPUX. Five electronic databases were used to identify studies for this systematic review: PubMed, Web of Science, Dentistry & Oral Science Source, Scopus and ScienceDirect, from January 15th, 1945 to January 10th, 2024. The Joanna Briggs Institute (JBI) tool was used to assess the risk of bias and the quality of the included reports and case series. A comprehensive search yielded 5,562 articles, of which 55 met the inclusion criteria. The total number of subjects studied in the included investigations was sixty-six. The subjects' ages varied from newborns to 61 years, with a mean age ± standard deviation of 71.23 ± 123.01 months. 50.7% were males and 49.3% were females. Most lesions presented normochromic color (24.24%), pedunculated base (31.81%), firm consistency (22.72%), with an average size of 1.20 cm, present on the dorsum of the tongue (31.81%) or anterior part of the alveolar border of the maxilla (30.30%). Treatment was carried out by surgical excision (78.46%) and half of the studies report that there were no recurrences. The cases described in the medical-dental literature provide valuable information to date on the clinicopathologic and immunohistochemical profile of OLH. Although it is a rare lesion, it should be considered as part of the differential diagnosis in newborns, infants, children and young adults with lingual and/or maxillary masses present in the midline.